Взаимодействие расплава кобальт–вольфрам со сформированной из алмазного порошка средой при высоком давлении и температуре - Луцак, Э.Н.; Романко, Л.А.; Бочечка, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Migration of cobalt and tungsten melt in the environment formed by the action of the pressure of 8 GPa on the diamond nanopowder UDD has been studied. Results of wetting of diamond compact by the cobalt-tungsten and copper-titanium melts in the same conditions are presented.